The Influence of Student Organizations on the Improvement of the Tridharma of Higher Education Students of the Faculty of Da'wah and Communication Uin Ar-Raniry - Dhiaul Fata; Fakhruddin Fakhruddin; Raihan Raihan (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2025)
Abstract: Student organizations are one of the important forums in supporting the non-formal learning process in higher education. Organizations not only function as a means of gathering and channeling aspirations, but also become a space for student self-actualization to improve academic abilities, leadership, research skills, and community service. This study aims to determine the effect of student organizations on improving the implementation of the Tridharma of Higher Education for students of the Faculty of Da'wah and Communication of UIN Ar-Raniry. This research was conducted in the field using a quantitative approach and descriptive design. The population in this study were students who were active in student organizations at the Faculty of Da'wah and Communication of UIN Ar-Raniry, with a total of 100 respondents. To determine the sample, the researcher used a random sampling technique. Data were collected through a closed questionnaire, then analyzed through validity, reliability, normality, linearity, homogeneity, t-test, coefficient of determination and with a simple linear regression method using the SPSS version 25 program. The results showed that student organizations had a positive and significant impact on the Tridharma of Higher Education, with a regression coefficient value of 0.475 and a significance level of 0.000 (p < 0.05). Keyword : Student organizations, tridharma of higher education, influence, linear regression.